PENGARUH CORPORATE IMAGE, USER IMAGE, DAN PRODUCT IMAGE TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN MOBIL TOYOTA CALYA PADA PT HADJI KALLA TOYOTA CABANG ALAUDDIN - Sitti Hartini Rachman; Otto Randa Payangan; Amiruddin Amrullah (Hasanuddin Journal of Applied Business and Entrepreneurship, 2020)
Lifestyle community growth accompanied by increased purchasing power makes income-increasing. This research aims to know the influence of Corporate Image, User Image, and Product Image against a Calya Toyota cars buying decision on PT Hadji Kalla Toyota branch of Alauddin. The data used in the study was obtained from questionnaires. Methods of analysis used is by the method of multiple linear regression analysis, using the test hypothesis that is a test of the F test and t. The results showed that variable Corporate Image, User Image, and Product Images are jointly significant influence on purchasing decisions of consumers with a level of significance of 5 percent. 74.6% of the variation in consumer purchasing decision variable can be explained by the variable Corporate Image, User Image, and Product Image, while the rest i.e. 25.4% of consumer purchase decisions are influenced by other variables not examined in this study.